EVALUATION OF TEACHER PERFORMANCE IN UNG LABORATORY ELEMENTARY SCHOOL - Nurfahmi; Djafri, Novianty; Qamar Badu, Syamsu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
The role of teachers is very important in ensuring student success, so the need for teacher performance evaluation is expected to improve the quality of education by helping teachers to realize their potential and be able to carry out their duties effectively and efficiently. This mini riser aims to find out the teacher performance evaluation that has been carried out by the principal of SD Laboratorium UNG. SD Laboratorium UNG is a school that has superior accreditation. The focus of this research is 1) The teacher performance evaluation model carried out by the principal at UNG Laboratory Elementary School, 2) The principal's strategy in improving teacher performance at UNG Laboratory Elementary School. This mini research was conducted using a qualitative approach, while the data collection techniques used were observation, interviews, and documentation, then the data presentation process was carried out using a descriptive approach in the form of words, written, or oral from the subjects observed, namely the principal, and teachers. The results of this study indicate that 1) The teacher performance evaluation model carried out by the principal at UNG Laboratory Elementary School is through performance evaluation meetings and supervision. 2) The principal's strategy in improving teacher performance at UNG Laboratory Elementary School is 1) The principal conducts a selection process in open recruitment of teachers. 2) The principal cooperates with certain parties. 3) The principal motivates and includes teachers to improve their professionalism by attending education and training (diklat), seminars, workshops, and the principal also conducts managerial supervision and clinical supervision of teachers.